The Mediating Role of Brand Trust in the Influence of E-WOM and Product Quality on Purchase Decisions for Natural Cosmetics in Bali - Sintiadewi, Ni Luh Gede Nita; Sara, I Made; Sitiari, Ni Wayan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid growth of the business world in the era of globalization also impacted the cosmetics industry. Consumers became more critical and selective in their purchase decisions, which were influenced by factors like electronic word of mouth (e-WOM), product quality, and brand trust. This study analyzed the impact of e-WOM and product quality on purchase decisions, with brand trust as an intervening variable. Using a quantitative method with a questionnaire, data were collected from 105 respondents in Bali. The results showed that e-WOM and product quality both had positive and significant effects on purchase decisions and brand trust. Brand trust partially explained the influence of e-WOM and product quality on purchase decisions. Future studies may explore additional factors and include more respondents for greater accuracy.